Design Of DC Motor Coupling System As Backup Electric Energy Based On Microcontroller - Putra Wahyudi Siregar; Solly Aryza; Siti Anisah (Sean Institute, 2024)
This research aims to design and analyze a DC motor coupling system as a backup electrical energy source controlled by a microcontroller. This system is designed to provide an efficient, reliable and economical backup energy solution, which can be used in various applications such as industrial, household and critical infrastructure. The design process includes integrating a DC motor with a microcontroller to regulate speed, monitor performance, and manage power automatically. Simulations and experimental testing were carried out to analyze the system performance in terms of energy conversion efficiency, operational reliability and response to various load conditions. The research results show that the DC motor coupling system controlled by a microcontroller is able to increase energy efficiency and reliability as a backup power source. The system can also be optimized to ensure maximum efficiency and stable performance. Sustainability evaluation and operational cost analysis show that this system has the potential for significant energy savings and low maintenance costs. Overall, this research contributes to the development of more efficient and adaptive backup energy source technology. This microcontroller-based DC motor coupling system offers a practical and innovative solution to meet backup energy needs in various sectors.This research aims to design and analyze a DC motor coupling system as a backup electrical energy source controlled by a microcontroller. This system is designed to provide an efficient, reliable and economical backup energy solution, which can be used in various applications such as industrial, household and critical infrastructure. The design process includes integrating a DC motor with a microcontroller to regulate speed, monitor performance, and manage power automatically. Simulations and experimental testing were carried out to analyze the system performance in terms of energy conversion efficiency, operational reliability and response to various load conditions. The research results show that the DC motor coupling system controlled by a microcontroller is able to increase energy efficiency and reliability as a backup power source. The system can also be optimized to ensure maximum efficiency and stable performance. Sustainability evaluation and operational cost analysis show that this system has the potential for significant energy savings and low maintenance costs. Overall, this research contributes to the development of more efficient and adaptive backup energy source technology. This microcontroller-based DC motor coupling system offers a practical and innovative solution to meet backup energy needs in various sectors.